DEMAND FUNTIONS FOR PAPER AND PAPER BOARD ONE OF FORESTRY WOOD PRODUCTS IN CHINA - Zeki M. Akrawee (Mesopotamia Journal of Agriculture)
This research was put to the demand functions for different kinds of paper and paper board in china, aiming to locate the factors which affect the quality demand of these commodities using linear and non linear functions. The results of the application illustrated that the 1/2 logarithm function for the base 10 on the right side was the best perfect state for writing and reading paper, and the logarithm function for the base 10 for both sides was the perfect state of news paper, and the multiple linear regression was the best state for other kinds of paper and paper boards, while the logarithm function for the base 10 for both sides was represent the state of gross paper and paper boards. With regard to import functions, the results indicated that the 1/2 logarithm function for the base 10 on the right side was represented the best perfect state for writing and reading paper, while the logarithm function for the base 10 for both sides was represented the perfect state for news paper, other kinds of paper and paper board and for the gross paper and paper board.